As Performance: Ethical and aesthetic considerations for therapeutic theatre. Issue 2 (1st October 2015) - Hodermarska, Maria; Landy, Robert; Dintino, Cecilia; Mowers, Dave; Sajnani, Nisha
This article presents observations and questions arising from an ongoing investigation into therapeutic theatre. Faculty involved in the training of NYU drama therapy students discuss selected productions presented as part of the As Performance series at NYU between 2011 and 2014. In so doing, critical questions are raised such as: how does performance transform the therapeutic encounter? How does performance contribute to healing? What are the aesthetic and ethical considerations that attend this genre? How does therapeutic theatre function as research that can reveal and simultaneously respond to human suffering? How does the experience of therapeutic theatre differ for key players involved: clients, drama therapists, drama therapy students and audiences? Our preliminary observations indicate that therapeutic theatre can be contextualized as a restaging of the drama between client and therapist, that playmaking is a primary process, and that there are benefits and challenges that proceed from working within a deeply intersubjective space. Aesthetic and ethical considerations are paramount in the therapeutic theatre process and require ongoing examination and study.